The Effectiveness of a Developed Interactive Electronic Unit Based on the Green Economy in Social Studies for Enhancing Achievement of Second Year Middle School Female Students and Their Attitudes Towards It - Al-Enazi, Hessa Abdullah; Alshumaimeri, Yousif Abdulrahman (Journal of Curriculum and Teaching Methodology, 2024)
The research aimed to analyze and develop an educational unit from the social studies curriculum for the second year of middle school in light of green economy concepts, and to design it as an interactive electronic module. The researchers employed both content analysis and quasi-experimental methods. The sample consisted of 60 female second-year middle school students. Data were collected using a content analysis form, an achievement test, and an attitude scale. The results showed statistically significant differences at the (α≤0.01) level between the mean post-test scores of the experimental group and the control group, in favor of the experimental group. Additionally, statistically significant differences were found at the (α≤0.01) level between the pre-test and post-test scores of the experimental group. Similar differences were noted in the attitude scale towards the unit between the pre-test and post-test scores of the experimental group, with the post-test scores being higher, attributed to the use of the unit. The results confirmed the effectiveness of the developed interactive electronic unit based on green economy concepts in social studies in enhancing achievement and attitudes among second-year middle school students. In light of these findings, the researchers recommended developing social studies textbooks in accordance with green economy concepts and its dimensions across all educational stages, and promoting the use of developed interactive electronic textbooks in various learning environments.
Keywords: interactive e-book; green education; social studies; achievement; attitudes